2017
DOI: 10.1099/jmm.0.000509
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of extended-spectrum-β-lactamase-producing Enterobacteriaceae in blood cultures using the ESBL NDP test in Cotonou, Benin

Abstract: The ESBL NDP test is rapid, relatively affordable and performed well in our setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…In Benin, several studies have reported the increasing evolution of the prevalence of broad-spectrum β-lactamase-producing enterobacteria in clinical infections [17][18][19]. But few studies have reported broad-spectrum β-lactamase-producing bacteria isolated simultaneously from external environment, kitchen environment, and food products.…”
Section: Introductionmentioning
confidence: 99%
“…In Benin, several studies have reported the increasing evolution of the prevalence of broad-spectrum β-lactamase-producing enterobacteria in clinical infections [17][18][19]. But few studies have reported broad-spectrum β-lactamase-producing bacteria isolated simultaneously from external environment, kitchen environment, and food products.…”
Section: Introductionmentioning
confidence: 99%
“…It is supposed that if the NDP test is implemented in routine practice, it might require additional costs, including personnel and laboratory costs, such as electricity, Eppendorf tubes, pipettes, and gloves. (20) There was a statistically significant reduction in LOT for patients who were given NDP test-guided antibiotic therapy in our randomized control trial. This might be due to the delay in the appropriate antibiotic intake in the group using standard culture-based therapy.…”
Section: Discussionmentioning
confidence: 61%
“…In the study by Duttaroy et al in India performed on 187 strains of E. coli and Klebsiella sp., 53 isolates (29.1%) were ESBL-producing (21). Also, among the ESBLproducing Enterobacteriaceae strains isolated from a hospital in France, a significant percentage of the isolated bacteria were E. coli (40.5%) (22). Therefore, it seems that the prevalence of ESBL-producing E. coli is relatively high in hospitals of Iran, which may be the cause of the high rate of resistance to antibiotics.…”
Section: Discussionmentioning
confidence: 99%